Characterization and reproducibility of canoe slalom simulated races: physiological, technical and performance analysis - Arnosti Vieira, N.; Dalcheco Messias, L. H.; Vollet Cardoso, M.; Ferrari, H. G.; Cunha, S. .; Terezani, D. R.; Manchado-Gobatto, F. B. (Journal of Human Sport & Exercise, 2015)
The aims of this study were to characterise and test the reproducibility of canoe slalom race simulations performed on two different days, analysing the physiological, technical and performance responses characteristic of the sport. Six high-performance male canoe slalom K1 athletes (age 17±2yrs) underwent two race simulations with an interval of 72 hours. The artificial course consisted of twelve gates. Each simulation was analysed the runtime, distance travelled, mean velocity; images were captured by the digital camera (JVC) and determined quantitative variables. Heart monitors (Polar, RS800x model) were used to record heart rate during race simulations and recovery; data were stored every 5 s, to determine the blood lactate concentration ([Lac]), blood samples were collected from the earlobe at rest and after 1, 3, 5, 7 and 9 min of race simulation (recovery). Tests of normality (Shapiro Wilk) and variance (Levene) were applied. The variables were compared using paired t-tests. Intraclass coefficient correlation (ICC) and Pearson product moment were used for relationship. In all cases, the level of significance was pre-fixed at 5%. Differences between the first and second simulations could not be noticed. Another important indicator was the high correlation found between the runtime (ICC=0.71), distance travelled (ICC=0.77), mean velocity (ICC=0.80) and total number of paddles (ICC=0.79). The lactate levels on minutes 3, 5, 7 and 9 also pointed towards strong correlations (ICC=0.88, ICC=0.90, ICC=0.95 and ICC=0.90 respectively), which may indicate that the adopted simulation model seems to be practicable and of great value to canoe slalom evaluations.